Helpful and Harmful Approaches to Integrating Religion and Spirituality into Mental Health Care: A National Survey of Current Clients’ Experiences in the United States - Oxhandler, Holly K. (Journal of religion and health, 2024)
This article describes a national sample of 989 current mental health clients’ views regarding whether and how their mental health care providers integrated the client’s religion/spirituality (RS) into treatment. Within the online Qualtrics survey, two open-ended items asked respondents what (if anything) the client perceived their therapist having done regarding the client’s RS that was (1) helpful/supportive or (2) hurtful/harmful. Participants also reported various ways therapists included the topic of RS in practice, if any. Nearly half freely described helpful ways their providers integrated the client’s RS, and half indicated it was not discussed or applicable. Although 9.6% described hurtful experiences, most indicated their provider had not done anything harmful related to integrating RS. Implications for practice and training across mental health disciplines are discussed.